Effect of mucilage on water properties in the rhizosphere monitored by 1H-NMR relaxometry - Brax, Mathilde; Buchmann, Christian; Schaumann, Gabriele Ellen (Microporous and mesoporous materials, 2018)
Mucilage produced at the root tips is a soil-born biohydrogel, whose framework is a three-dimensional polysaccharidic polymer network, which can contain over 90% water. The specific biohydrogel properties of mucilage, such as volumetric expansion and shrinkage, affect soil mechanical and hydraulic properties. Still, the physico-chemical mechanisms governing the interactions between mucilage and the porous soil system remain mostly unclear. To our best knowledge, no currently applied method allows the distinction between biohydrogel phases and pore water in the porous soil system. In this work, we used 1H NMR relaxometry to analyze the presence and properties of biohydrogels in soil. Mucilage in soil leads to a hierarchical pore structure, consisting of the polymeric biohydrogel network surrounded by the surface of soil particles. Water molecules entrapped in mucilage-containing soils revealed an accelerated bulk relaxation and a higher surface relaxivity in comparison with soils not containing mucilage. In model soils, we quantified the gel effect, here defined as the influence of mucilage on proton relaxation. The difference between transversal and longitudinal relaxation rates was plotted as a function of the reciprocal diameter of the model soil particles for soils containing and not containing mucilage. The gel effect was thereby characterized by an accelerated bulk relaxation and an accelerated surface relaxation, traduced respectively by an increased y-intercept and an increased linear coefficient for mucilage-containing soil.